Answer:
i can't sorry
Explanation:
I didn't really pay attention in that class
Answer: if the mass is doubled, the force of gravity is doubled, meaning it decreases. If the distance is doubled, the force of gravity is 1/4 as strong as before
Explanation:
v = √ { 2*(KE) ] / m } ;
Now, plug in the known values for "KE" ["kinetic energy"] and "m" ["mass"] ;
and solve for "v".
______________________________________________________
Explanation:
_____________________________________________________
The formula is: KE = (½) * (m) * (v²) ;
_____________________________________
"Kinetic energy" = (½) * (mass) * (velocity , "squared")
________________________________________________
Note: Velocity is similar to speed, in that velocity means "speed and direction"; however, if you "square" a negative number, you will get a "positive"; since: a "negative" multiplied by a "negative" equals a "positive".
____________________________________________
So, we have the formula:
___________________________________
KE = (½) * (m) * (v²) ; to solve for "(v)" ; velocity, which is very similar to the "speed";
___________________________________________________
we arrange the formula ;
__________________________________________________
(KE) = (½) * (m) * (v²) ; ↔ (½)*(m)* (v²) = (KE) ;
___________________________________________________
→ We have: (½)*(m)* (v²) = (KE) ; we isolate, "m" (mass) on one side of the equation:
______________________________________________________
→ We divide each side of the equation by: "[(½)* (m)]" ;
___________________________________________________
→ [ (½)*(m)*(v²) ] / [(½)* (m)] = (KE) / [(½)* (m)]<span> ;
</span>______________________________________________________
to get:
______________________________________________________
→ v² = (KE) / [(½)* (m)]
→ v² = 2 KE / m
_______________________________________________________
Take the "square root" of each side of the equation ;
_______________________________________________________
→ √ (v²) = √ { 2*(KE) ] / m }
________________________________________________________
→ v = √ { 2*(KE) ] / m } ;
Now, plug in the known values for "KE" ["kinetic energy"] and "m" ["mass"];
and solve for "v".
______________________________________________________
Answer:
H = Vy t - 1/2 g t^2 height of an object with an initial "vertical" velocity
at t sec after firing
Vy = 78 m/s * sin 40 = .643 * 78 m/s = 50.1 m/s
H = 50.1 * 6 - 1/2 * 9.8 * 6^2 = 300 m - 176 m = 124 m
<span>Actually newtons third law says for every action there is an equal and opposite reaction, Hence here in this case, the diver diving of a raft is the action, after which surely reaction should come in the form where the raft and the driver will rebound with same speed back, and hence here the action force is diving and reaction force is rebounding from the diving place, with same intensity.</span>